Conniff & Davis, Africans In The Americas - Jaja, Cheedy (Teaching History: A Journal of Methods, 1996)
Africans in The Americas is a useful addition to the growing revisionist literature on the disasporic experience of Africans. The object of the authors is clear and concise," … to convey to the college student and the informed reader the intellectual challenge and excitement of the recent research that has greatly sharpened our understanding of the myriad of ways that the African-American experience has shaped today’s world." True to this purpose, the text is the outcome of a collaborative project involving seventeen historians working at the advanced edges of their field.